Uji coba pembuatan sol karet cetak sesuai SII 0944 – 84 sistem cetak “hand press” - Penny Setyowati (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1992)
The trial on making of rubber sole fulfilling the SII 0944 – 84 with hand press molding system was using rubber compound on the formula of : RSS I 100 parts; Reclain rubber 30; ZnO 3; Carbon black 60; Paraffinic oil 6; Stearic acid 2; PBN 1; MBT 0,5; MBTS 0.5; TMT 1 and Sulfur 2. The vulcanization condition with time interval 0.5 minutes. Physical testing of rubber sole trial result, statistical evaluation with CRD method for determining vulcanization time for resulting optimal physical testing. Optimal physical test value was reached on the time of vulcanization 6 to 7 minutes and temperature of vulcanization between 150-1600 C.